تعليل النصوص الشرعية في الطب النبوي: دراسة تحليلية نقدية - Ahmad Akram Muhammad Rabbi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aims to investigate about the Traditions of Prophetic Medical Issues. This study discusses about the minsundertanding in interaction with hadith pertaining with medical issues. The hadith of Prophet come from a variety way, which it is strongly related with certain situations or customs that could influence the background of hadith. This conflict has been widely discussed by Islamic scholars under the topic Tasarrufat Nabawiyyah. There are two basic elements in Prophetic Medical issue: the first element is about Tibb al- Qalb and its source come from Allah, and the second element is Tibb al-Badan that comes from the scientific experiments by human. This study applies some methodologies that combine between analytical studies and crtitical studies. This study gathers information by collecting some books, articles, and information from electronic media which were then it will be analyzed for the strongest justification. This study found that the reason behind of this misunderstanding is because people are interacting and applying the Prophetic Medicine in their life without understanding legal methods and principles in interaction with the Prophetic Tradition.